2012
DOI: 10.1021/ja3039807
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Alkene Arylation with Diaryliodonium Salts

Abstract: Alkenes and arenes represent two classes of feedstock compounds whose union has fundamental importance to synthetic organic chemistry. We report a new approach to alkene arylation using diaryliodonium salts and Cu catalysis. Using a range of simple alkenes, we have shown that the product outcomes differ significantly from those commonly obtained by the Heck reaction. We have used these insights to develop a number of new tandem and cascade reactions that transform readily available alkenes into complex arylate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(96 citation statements)
references
References 42 publications
2
92
0
2
Order By: Relevance
“…35 The methoxy functionalized ketones 8h and 8b were also transformed into cyclic alkenes 1h and 1b in 93 and 76% yields, respectively (entries 2 and 3). 13,36,37 The benzoyl, tosyl, Fmoc and acetyl protected amino ketones (7c-f) were smoothly converted into desired olefinic substrates (1c-f) in good yields (entries 4-7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…35 The methoxy functionalized ketones 8h and 8b were also transformed into cyclic alkenes 1h and 1b in 93 and 76% yields, respectively (entries 2 and 3). 13,36,37 The benzoyl, tosyl, Fmoc and acetyl protected amino ketones (7c-f) were smoothly converted into desired olefinic substrates (1c-f) in good yields (entries 4-7).…”
Section: Resultsmentioning
confidence: 99%
“…few crystals) at 130 o C. The crude product was purified by flash column chromatography (20-40% EtOAc in hexane) giving alkene 1h. 36 Yield: 1.702 g (95%); colorless oil. Under inert atmosphere N 2 , NaH (6.24 g, 260 mmol, 60% in mineral oil) was washed with anhydrous hexanes (3 × 20 mL).…”
Section: 8-dihydronaphthalen-1-yl Acetate (9g)mentioning
confidence: 99%
“…65 Formation of two alkene isomers was observed (78 and 79) and the selectivity was influenced by the structure of the alkene and the iodonium salt. Preliminary studies showed that a carbocation-type mechanism was operated in these reactions.…”
Section: Scheme 31mentioning
confidence: 99%
“…[54][55][56][57][58][59][60][61][62][63][64][65][66][67] Utilizing this concept, several syntheses of diverse heterocyclic skeletons were developed in the last few years in our and other laboratories. The copper catalyzed synthesis of new oxazoline derivatives (89) from propargyl amides (88) and diaryliodonium salts was recently developed by our research group.…”
Section: 2 Copper Catalyzed Cyclization Of Unsaturated Compounds mentioning
confidence: 99%
“…The Mizoroki-Heck reactions are originally catalyzed by palladium [1][2][3][4][5][6]. Other transition metals, such as nickel, cobalt, copper, gold, and iron, are also active catalysts for Heck-type reactions [26][27][28][29][30][31][32][33]. The visible light-induced Pd-catalyzed Mizoroki-Heck reactions between sterically hindered alkyl halides and vinyl arenes have been accomplished, as well [34,35].…”
Section: Introductionmentioning
confidence: 99%